2013
DOI: 10.1007/s00540-013-1727-0
|View full text |Cite
|
Sign up to set email alerts
|

Is preoperative period associated with severity and unexpected death of injured patients needing emergency trauma surgery?

Abstract: PurposeEarly operative control of hemorrhage is the key to saving the lives of severe trauma patients. We investigated whether emergency room (ER) stay time (time from the ER to the operating room [OR]) is associated with trauma severity and unexpected trauma death (Trauma and Injury Severity Score [TRISS] method-based Probability of survival [Ps] ≥0.5 but died) of injured patients needing emergency trauma surgery. MethodsWe performed a retrospective review of call trauma patients requiring emergency surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Twenty-six studies have been considered for secondary outcome [ 6 , 17 – 20 , 23 , 24 , 26 43 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six studies have been considered for secondary outcome [ 6 , 17 – 20 , 23 , 24 , 26 43 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged ED times for severely injured trauma patients have been shown to increase mortality. 51 Quick airway control, chest drain insertion, and initiation of blood transfusion can be performed before transport to the OT. More time-consuming procedures, such as placement of central lines or arterial lines, should not be allowed to delay transfer.…”
Section: Ed and Airway Managementmentioning
confidence: 99%
“…Previous studies have shown that rapid patient transfer to a trauma center and rapid initiation of definitive care, such as surgery or transarterial embolization (TAE), strongly influence survival among severely injured patients [4][5][6][7][8][9]. The preoperative time course, such as prehospital length of stay (LOS), emergency department (ED) LOS, and total time to surgery or TAE, is therefore regarded as an important parameter in trauma care [10,11].…”
Section: Introductionmentioning
confidence: 99%